A solution to the ecological inference problem reconstructing individual behavior from aggregate data - King, Gary 1958- (Princeton Univ. Press, 1997)
This book provides a solution to the ecological inference problem, which has plagued users of statistical methods for over 75 years: How can researchers reliably infer individual-level behavior from aggregate (ecological) data? In political science, this question arises when individual-level surveys are unavailable (for instance, local or comparative electoral politics), unreliable (racial politics), insufficient (political geography), or infeasible (political history). This ecological inference problem also confronts researchers in numerous areas of major significance in public policy, and other academic disciplines, ranging from epidemiology and marketing to sociology and quantitative history. Although many have attempted to make such cross-level inferences, scholars agree that all existing methods yield very inaccurate conclusions about the world. In this volume, Gary King lays out a unique - and reliable - solution to this venerable problem.
Keywords: Aggregatie; Inferencia; Inférence (Logique); Politieke wetenschappen; Science politique - Méthodes statistiques; Inference; Political statistics; Interferenz; Interferenz -- Ökologie; Umweltschutz; Statistik